RESPONSE OF POTATO GROWTH AND YIELD ON FIRST GENERATION (G1) IN VARIOUS PLANTING MEDIA COMPOSITIONS - Muhsanati Muhsanati; Irfan Suliansyah; Ogy Saputra Syafril (JERAMI : Indonesian Journal of Crop Science, 2024)
Potatoes are one of the horticultural commodities that contain carbohydrates, proteins, and other nutrients, making them a potential crop to support diversification and food security programs. This study aims to find a suitable planting medium to overcome the limitations and provide high-quality potato seeds. The research was conducted from March to August 2023 in Alahan Panjang, Solok. The treatments involved various compositions of cocofiber (CF) and cocopeat (CP) planting media arranged in a Completely Randomized Design with 6 treatments and 4 replications, namely the compositions: CF 100%, CP 100%, CF 20% + CP 80%, CF 40% + CP 60%, CF 60% + CP 40%, and CF 80% + CP 20%. The obtained data were statistically analyzed using the F-test and further analyzed with the DNMRT test at a 5% significance level. The results showed that, in general, the use of 100% cocopeat planting medium was the best composition, while the 80% cocopeat + 20% cocofiber composition provided the best vegetative growth.